Farmacevtske kompetence s področja laboratorijske medicine - Božič, Borut (Farmacevtski vestnik, 2025)
The regulation of the pharmaceutical profession derives from Directive 2005/36/EC on the recognition of professional qualifications, which was updated in 2024. The training program for pharmacists also includes ‘general and Applied Biochemistry (Medical),’ which is known as clinical biochemistry. The latter is the largest branch of laboratory medicine – the activity of analyzing human biological samples to determine the health status of an individual in prevention, diagnosis, treatment monitoring, and disease prognosis. This area is still not well known in the professional community as a competence of pharmacists. The article describes the characteristics of the development of laboratory medicine in the European and Slovenian context with the milestones in the development of clinical chemistry and the organization of its education in Slovenia, which began as part of pharmacy studies. The competency aspects of pharmacists in the field of laboratory diagnostics are particularly emphasized.
Keywords: Diagnostika; Farmacija; izobraževanje; Klinična biokemija; kompetence/kompetenčni modeli; Laboratorijska medicina